2014
DOI: 10.1002/ase.1446
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of three‐dimensional digital animation in teaching human anatomy in an authentic classroom context

Abstract: Three-dimensional (3D) digital animations were used to teach the human musculoskeletal system to first year kinesiology students. The purpose of this study was to assess the effectiveness of this method by comparing two groups from two different academic years during two of their official required anatomy examinations (trunk and upper limb assessments). During the upper limb section, the teacher used two-dimensional (2D) drawings embedded into PowerPoint(®) slides and 3D digital animations for the first group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
2
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 38 publications
2
93
2
4
Order By: Relevance
“…Making the models available for students to interact with using 3D visualization technology facilitates active user control to rotate and manipulate structures for visualization from multiple perspectives to develop visuospatial abilities essential to medical practice (Azer and Azer, ; Wainman et al, ). Three‐dimensional computer‐based visualizations have been shown to enhance spatial abilities in some studies (Ruisoto et al, ; Müller‐Stich et al, ; Hoyek et al, ; Kong et al, ), but not in others (Hu et al, ; Keedy et al, ; Khot et al, ). In addition, it has been reported that the effectiveness of educational models is related more to the mode of delivery and integration, rather than the model itself per se (Nnodim, ; Wilson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Making the models available for students to interact with using 3D visualization technology facilitates active user control to rotate and manipulate structures for visualization from multiple perspectives to develop visuospatial abilities essential to medical practice (Azer and Azer, ; Wainman et al, ). Three‐dimensional computer‐based visualizations have been shown to enhance spatial abilities in some studies (Ruisoto et al, ; Müller‐Stich et al, ; Hoyek et al, ; Kong et al, ), but not in others (Hu et al, ; Keedy et al, ; Khot et al, ). In addition, it has been reported that the effectiveness of educational models is related more to the mode of delivery and integration, rather than the model itself per se (Nnodim, ; Wilson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…When compared to 2D representations of human structures, the use of 3Dv results in improved outcomes in terms of understanding spatially demanding anatomical knowledge (Hoyek et al, 2014) and student satisfaction (Beermann et al, 2010;Hoyek et al, 2014). However, improved outcomes only seem to occur with respect to complex anatomy (Beermann et al, 2010;Hoyek et al, 2014). Though an excellent teaching tool, 3Dv lack the physical experience of a cadaver, but it may be possible to overcome this barrier if virtual models can be converted into 3Dp models.…”
Section: Experimental Researchmentioning
confidence: 99%
“…3D models in any form are preferred over 2D images (Hoyek et al, 2014;Li et al, 2015). This impact is greater in 3Dp models compared to 3Dv models (Li et al, 2015), with students reporting greater pleasure, personal learning effect and confidence in explaining to peers.…”
Section: Experimental Researchmentioning
confidence: 99%
“…According to actual needs and module design, function of this system is designed in the following way: (1) browsing of courses and experiment conditions; (2) downloading of all sorts of teaching resources; (3) exchanging of questions and answers between teachers and students online; (4) uploading and sharing of students' works; and (5) assignment and viewing of homework. Figure 3 shows the diagram of functional structure of the intelligent 3D teaching system.…”
Section: System Function Designmentioning
confidence: 99%
“…According to relevant investigations, professional designers of digital animation featured by the mastery of audiovisual language, a solid foundation of painting, and the proficiency in operating computers and other related equipment are rare resources in the market [1]. The virtual feature of animation, a fantasy art, is shown not only in the extraordinary, unique, unstrained, and vigorous story, but also in the unconventional and exaggerated audiovisual style, specifically, reflected in the imaginary scene setting, virtual figure modeling, and transformation of sound elements [2]. Thus, the strong formal and unreal sense makes animation become the representative of fictional art.. Generally, the current teaching concerning digital animation fully and correctly interprets basic concepts and theories, but lacks a strong professional pertinence.…”
Section: Introductionmentioning
confidence: 99%